Computer simulation of stone falls and rockfalls - Petje, Urška; Ribičič, Mihael; Mikoš, Matjaž (Acta geographica Slovenica, 2005)
The paper gives an overview of the literature on available computer (simulation) models of stone falls and rockfalls, divided into 2D and 3D models. 2D models consider single blocks in the rock-fall mass as lumped mass or a rigid body, and are used to assess the single rockfall runout distance. Opposed to the 2D models, 3D models are composed not only of a dispositional model (depicting rockfall source areas) and friction model (determination of deposition areas and maximum runout distances), but also from a trajectory model (determination of travel areas).